A comparative study of cascade H-bridge multilevel voltage source inverter and parallel inductor multilevel current source inverter - Nik Fasdi Nik Ismail; Norazlan Hashim; Dalina Johari (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
This paper presents the analysis study between multilevel inverters that are often classified into multilevel voltage source and multilevel current source inverters.  For multilevel voltage source inverter (MVSI), the specific topology studied for this work is the Cascaded H-Bridge MVSI.  Whereas, the multilevel current source inverter (MCSI) is based on Paralleled Inductor Configuration MCSI.  For this study, the analysis between these converters are done with respect to the number of components, the advantages and disadvantages of each converters during performing inverter operation. In term of output voltage and current quality, the percentage of the Total Harmonic Distortion (THD) are measured and compared for both topologies.  MATLAB/Simulink software has been used in this research to design and simulate in order to study the performances of both inverters.